Beyond the Sacred Walls: Reimagining Pesantren's Architecture of Islamic Moderation - Ubaidillah, Ubaidillah; Fauzinudin Faiz, Muhammad (Ulumuna, 2025)
This study examines the epistemological transformation of traditional Islamic boarding schools (pesantren) in fostering Islamic moderation within contemporary Indonesian society. Through a qualitative approach combining phenomenological and critical-hermeneutical analysis, this research investigates how pesantren reimagines its educational and social roles beyond conventional boundaries. The study reveals that pesantren's adaptive strategies in promoting moderate Islam operate through three interconnected dimensions: epistemological reconstruction, institutional transformation, and social engagement. Drawing from extensive fieldwork in East Java's prominent pesantren, the findings demonstrate how these institutions effectively integrate traditional Islamic wisdom with modern educational approaches while maintaining their distinctive cultural identity. The research highlights pesantren's unique capability in developing a contemporary framework for Islamic moderation that successfully counters religious radicalism while preserving indigenous Islamic traditions. This study contributes to the broader discourse on religious moderation by presenting Pesantren's innovative approach to bridging traditional Islamic values with modern societal demands.